A Multicenter Large-Scale Retrospective Analysis of the Correlation between Body Mass Index and All-Cause Mortality in Patients with Type 2 diabetes Mellitus: A Seven-Year Real-World Study. (3rd July 2019) - Ma, Jihong; Wang, Xiaodong; Zheng, Mao; Yu, Haizhu; Ma, Junmin; Li, Xiaohang; Pan, Jingye; Huang, Yueyue
ABSTRACT: Aims : To investigate the association between body mass index (BMI) and all-cause mortality in patients with type 2 diabetes mellitus (T2DM) and to determine any sex-specific differences in this association. Methods : We retrospectively enrolled patients with T2DM and investigated the annual death data for seven years starting from 2010. All-cause mortality was calculated using Life Tables analysis. Multivariate Cox proportional hazards analysis was performed to identify the association between BMI and mortality. Results : During a mean survey period of 7.33 ± 1.42 years (X± SD), 996 of the 17259 patients enrolled died, resulting in an all-cause mortality rate of 5.77%, with no significant difference between women and men (6.04% vs . 5.56%; x 2  = 1.766, P = 0.184). The top three causes of death were ischemic heart disease, cerebrovascular disease, and chronic kidney failure. A total of 87, 266, 332, and 311 patients with a BMI of <18.5, 18.5–23.99, 24.0–27.99, and ≥28.0 kg/m 2, respectively, died, with the corresponding mortality rate calculated at 15.45%, 3.30%, 5.80%, and 10.70%, respectively. The BMI value associated with the highest all-cause mortality was <18.5 kg/m 2, but this association was only significant in women aged <50 years (HR: 3.12; 95% CI, 1.62–4.34; P < 0.001). Conclusions : In patients with T2DM, a low BMI in women aged <50 years predicted high all-cause mortality.